Pengaruh Influencer Marketing Dan Live Streaming Terhadap Keputusan Pembelian Di Brand Gwenza - Rehisya Febiyanti; Ridho Riadi Akbar; Rama Chandra Jaya (IKRAITH-EKONOMIKA, 2026)
This research examines the contribution of influencer marketing and live streaming to consumers' purchase decisions at Brand Gwenza. A quantitative causal design was applied. Primary data were obtained from 104 consumers selected through purposive sampling because they had been exposed to, watched, or purchased Gwenza products through digital marketing channels. SPSS was used to assess instrument quality, regression assumptions, multiple linear regression, hypothesis tests, and the coefficient of determination. The results demonstrate that both influencer marketing and live streaming have positive and statistically significant effects on purchase decisions. Influencer credibility, competence, attractiveness, and perceived similarity strengthen consumer confidence, while live sessions support decision making through product demonstrations, two-way communication, and immediate responses. Together, the two predictors explain 84.3% of the variance in purchase decisions. The standardized beta coefficients indicate that influencer marketing provides the larger relative contribution. Accordingly, Brand Gwenza should prioritize relevant influencers and improve information clarity, streamer responsiveness, and audience interaction during live streaming.